Navigating Government Information System Efficacy: Insights from Human Resource Information System Implementation - Noerman, Teuku; Sandy Yuliaji, Eliana; Riana, Nia (Profit: Jurnal Adminsitrasi Bisnis, 2025)
This investigation delved into the effectiveness of the Human Resource Information Systems (HRIS) in enhancing Information Quality, System Quality, System Utilization, User Satisfaction, and Employee Performance. Employing a survey with a Likert rating approach among 138 respondents from the Directorate General of Legislation, the study used Partial Least Squares Structural Equation Modeling (PLS-SEM) via SmartPLS software version 3.2.8 for data analysis. The findings demonstrate that HRIS significantly bolsters system usage and user satisfaction, improving employee performance, particularly during the digital transformation necessitated by the COVID-19 pandemic. Digital-centric work system modification as the success of human resource management in adopting digital transformation, guided by HRIS steps to form a theoretical structure designed to ensure whether organizational performance can reach its potential after conversion to a digital system. This study depicted that workforce efficiency was attainable alongside alterations in human resource management through the digital shift of work operations, as denoted by HRIS benchmarks. An efficient digital work system could augment employee workflows, thereby enhancing satisfaction among system users, which might influence employee performance tiers. The insights from this study are anticipated to bolster subsequent inquiries and foster development in the field.